2010
DOI: 10.1111/j.1365-2435.2010.01783.x
|View full text |Cite
|
Sign up to set email alerts
|

Post-fledging recruitment in relation to nestling plasma testosterone and immunocompetence in the spotless starling

Abstract: Summary1. Social and ecological conditions experienced by individuals during early life can strongly influence their development and survival. Nestlings of many species present important variations in plasma androgens that can be associated with begging and sibling competition and may translate into fitness effects, since broods with higher testosterone (T) production may have better body condition and higher fledging success. However, the positive effects of androgens may be counterbalanced by a reduction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 80 publications
4
32
1
Order By: Relevance
“…We found that CMI, as well as several hematological traits, such as basophils and monocytes, decreased as the breeding season advanced, as is often the case in other studies (Sorci et al 1997;López-Rull et al 2011). We have previously shown a negative effect of clutch laying date on nestling body condition in the same study population (Muriel et al 2015a).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…We found that CMI, as well as several hematological traits, such as basophils and monocytes, decreased as the breeding season advanced, as is often the case in other studies (Sorci et al 1997;López-Rull et al 2011). We have previously shown a negative effect of clutch laying date on nestling body condition in the same study population (Muriel et al 2015a).…”
Section: Discussionsupporting
confidence: 62%
“…The nestling period lasts about 21-22 d (Cramp 1998). Females can lay up to two clutches per season, the first in early April and the second about the end of May in our study area (López-Rull et al 2011). A replacement clutch could be laid as a result of the loss of the first clutch by predation or intraspecific competition (Müller et al 2007;Muriel et al 2015a).…”
Section: Study Species and Sitementioning
confidence: 99%
“…Nestlings mounting the highest PHA responses had the highest inter-annual return rates, suggesting that, in an ecological context, optimal responsiveness lies closer to the maximum than usually thought. Indeed, recent studies have found positive associations between PHA responsiveness and recruitment in local populations (Cichoń and Dubiec 2005, Moreno et al 2005, López-Rull et al 2011); however, our study is unique in that we were able to follow individuals from multiple cohorts to analyze longevity as a combination of local recruitment and subsequent inter-annual survival within the population, a major determinant of fitness (McCleery et al 2004, see also Cam et al 2002). Life-history theory posits that, within and among species, investment in immune function should vary with pace of life (Ricklefs and Wikelski 2002, Lee 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Bowers 2009-2011, unpublished data). Cutaneous immune response, as assessed by the PHA assay, is also a positive predictor of nestling survival in other species ( [39][40][41], but see Butler et al [42]). Thus, the increased body mass and condition index of sons and increased PHA response of daughters produced by LPSinjected females should afford them a substantial fitness advantage in that they are more likely to survive and reproduce than offspring of control females.…”
Section: Discussionmentioning
confidence: 99%